A Rare Primary Breast Angiosarcoma with Bone Metastasis: A Case Report - Sari , Rupita; Kiki A. Rizki; Anglita Yantisetiasti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Angiosarcoma is a rare and aggressive malignant tumor originating from endothelial cells. Primary breast angiosarcoma (PBA) is exceedingly uncommon, accounting for less than 1% of all breast malignancies. Bone metastasis from PBA is even rarer, making it a unique clinical entity. Case presentation: We present the case of a 37-year-old woman who initially presented with a rapidly enlarging breast mass. A biopsy confirmed the diagnosis of PBA, and she underwent a modified radical mastectomy followed by radiotherapy. Seventeen months later, she developed progressive lower extremity weakness and urinary and bowel incontinence. Imaging revealed a spinal metastasis at the Th4-Th6 level. Biopsy and immunohistochemistry confirmed metastatic angiosarcoma. The patient underwent laminectomy and posterior stabilization. Conclusion: This case highlights the rarity and aggressive nature of PBA with bone metastasis. It emphasizes the importance of early detection, comprehensive treatment, and long-term surveillance in managing this challenging disease. Further research is needed to understand the underlying mechanisms and develop effective therapeutic strategies for PBA with bone metastasis.